MELATIH KEMAMPUAN MENCIPTA SISWA MELALUI PEMBELAJARAN BERBASIS PROYEK-STEM - Rosa Yoeliana; Yennita; Mitri Irianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Students who can compete and follow the development of science and technology in the 21st century are students who have skills with high-level and creative thinking. Hence, students can practice their thinking skills to think and reason to find out the solutions to answer complex problems that will come possibly. It can be seen from the cognitive skills based on the indicators of creative skill. To improve this skill, it is necessary for the researchers to apply innovative learning-oriented high-order thinking skills. One of them is STEM as project-based learning (Pjbl-STEM). The purpose of the research is to see the students' higher-order thinking skills on the indicators of creative skill with Pjbl-STEM. The type of research used is quasi-experimental research with a non-equivalent post-test-only control group design. The method of data collection is collected by providing a test with a research instrument of a higher-order thinking skills questionnaire on the indicators of creative skill. The analysis technique used descriptive analysis. The results showed that the difference between the average class applying Pjbl-STEM and the class applying conventional learning was positive.